2021
DOI: 10.1002/inf2.12273
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated carbon nanotubes with high electrocatalytic activity for oxygen evolution in acidic conditions

Abstract: Since most electrocatalysts for oxygen evolution reaction (OER), except for precious metal oxides RuO2 and IrO2, are unstable in harsh acidic solutions, it is highly desirable to develop high‐performance OER electrocatalysts for acidic media, though it is still a big challenge. Herein, we report a simple strategy to produce carboxyl‐enriched multiwalled carbon nanotubes (COOH‐MWNTs) that exhibit stable and high electrocatalytic activities for OER in acidic solutions, showing an overpotential at a current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Newly developed OER catalysts can be classified into two types. Metal-free nanomaterials such as carbon nanotube (CNT), graphene, and boron nitride are reported as efficient OER electrocatalysts; however, these catalysts always require multi-step functionalization and are sensitive to pH in the system [7,8]. On the other hand, first-row transition metal-(Mn, Fe, Co, Ni, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Newly developed OER catalysts can be classified into two types. Metal-free nanomaterials such as carbon nanotube (CNT), graphene, and boron nitride are reported as efficient OER electrocatalysts; however, these catalysts always require multi-step functionalization and are sensitive to pH in the system [7,8]. On the other hand, first-row transition metal-(Mn, Fe, Co, Ni, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…When the CNT content was 9 wt.%, the contact angle of CNT-PI film was increased to 81.17°, which is 45.62% higher than that of pure PI film. However, C-CNT was not so effective in improving the contact angle of PI films because the carboxyl group in C-CNT was hydrophilic, so the hydrophobicity of C-CNT was not as good as that of CNT [ 50 ]. As a result, the contact angle of C-CNT/PI films only increased to 76.23 when the content of C-CNT was 9%, which was 36.76% higher than that of pure PI films.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further research and improvements are still needed to realize largescale industrial production and application. 57,176 Over the recent years, the interface engineering strategy has emerged as an extremely efficient approach to construct electrocatalysts with abundant and highly-active interfaces, which has broad application prospects. This review provided a systematic overview of the promising interface engineering strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The development of catalysts with ultrahigh current density, low toxicity, high stability, and low cost is a crucial prerequisite for industrial hydrogen production, and most of the reported well‐designed catalysts cannot meet all the above requirements simultaneously. Therefore, further research and improvements are still needed to realize large‐scale industrial production and application 57,176 . Over the recent years, the interface engineering strategy has emerged as an extremely efficient approach to construct electrocatalysts with abundant and highly‐active interfaces, which has broad application prospects.…”
Section: Discussionmentioning
confidence: 99%